Enhancing Work Discipline through Leadership, Culture, and Communication: Meningkatkan Disiplin Kerja melalui Kepemimpinan, Budaya, dan Komunikasi - Firdaus, Vera; Damayanti, Nadia (Indonesian Journal of Law and Economics Review, 2024)
This study investigates the collective impact of leadership, work culture, and communication on work discipline among 92 employees at PT. Surya Pratista Hutama. Using quantitative methods and a Likert scale questionnaire, the research finds that effective leadership, supportive work culture, and clear communication significantly enhance employee discipline. These results highlight the importance of fostering these organizational factors to improve overall discipline and performance within PT. Surya Pratista Hutama, suggesting implications for managerial practices and organizational policies aimed at strengthening leadership, culture, and communication strategies. Highlight: Leadership's pivotal role in fostering work discipline. Organizational culture's influence on employee behavior. Communication strategies and their impact on workplace discipline. Keywords: Work discipline, leadership influence, organizational culture, communication impact, quantitative research